Hormonal characteristics of androgen status and their relationship with the anthropometric and metabolic parameter in men depending on the severity of hypertension - S. V. Yankovskaya; O. I. Kuzminova; B. B. Pinkhasov; Yu. V. Lutov; V. G. Selyatitskaya (Acta Biomedica Scientifica, 2022)
Background. According to the literature data, long-term and poorly controlled hypertension (HTN) leads to target organs damage, and in some cases, to the development of associated diseases, the severity of which in men may be partly due to the characteristics of the androgenic status.The aim: to reveal the features of hormonal indicators of androgen status and their relationship with the anthropometric and metabolic characteristics of the therapeutic clinic male patients, depending on the severity of HTN.Materials and methods. 296 men aged 59,0 [54,0; 65,0] years with confirmed HTN were examined. All study participants in the morning on an empty stomach underwent anthropometry, determination of metabolic and androgenic status, and assessment of comorbid burden. Depending on the severity of hypertension, all patients were divided into two groups (G): G1 (n = 134) – patients with hypertension without a history of coronary artery disease or stroke; G2 (n = 162) – patients with hypertension with a history of ischemic heart disease (IHD) and/or stroke.Results. In male patients of G2 with severe HTN, a decrease in the levels of free testosterone (FT) and, to a greater extent, dehydroepiandrosterone sulfate (DHEA-S), as well as total cholesterol, high and low density lipoproteins, was revealed. The correlation analysis performed revealed statistically significant negative correlations between the levels of total testosterone (TT) and FT with body mass index, the value of the ratio of waist circumference to hips, only the level of FT – with the presence of IHD, chronic heart failure (CHF), disorders of carbohydrate metabolism and abdominal type of fat distribution, and the level of DHEA-S – with the presence of IHD and CHF.Conclusion. A decrease in FT and DHEA-S is associated with early progression of atherosclerosis and the risk of developing HTN-associated cardiovascular events, which can aggravate the course of HTN.